Seapower states : maritime culture, continental empires and the conflict that made the modern world - Lambert, Andrew D., 1956- (Yale University Press, 2018)
Andrew Lambert, author of The Challenge: Britain Against America in the Naval War of 1812--winner of the prestigious Anderson Medal--turns his attention to Athens, Carthage, Venice, the Dutch Republic, and Britain, examining how their identities as "seapowers" informed their actions and enabled them to achieve success disproportionate to their size. Lambert demonstrates how creating maritime identities made these states more dynamic, open, and inclusive than their lumbering continental rivals. Only when they forgot this aspect of their identity did these nations begin to decline. Recognizing that the United States and China are modern naval powers--rather than seapowers--is essential to understanding current affairs, as well as the long-term trends in world history. This volume is a highly original "big think" analysis of five states whose success--and eventual failure--is a subject of enduring interest, by a scholar at the top of his game